The Effectiveness And Efficiency of The Routine Program of The Lazis Al-Haromain Ta'lim Assembly in Kediri City in Increasing Ziswaf Donors - Riza Sofiana Dewi; Zuraidah Zuraidah (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2023)
Majelis Ta'lim is defined as teaching or education. Majelis Ta'lim is a programme that takes place regularly and not routinely. There is an amil zakat institution in Kediri City that has a routine programme of majelis ta'lim, namely LAZIS Al-Haromain. Distribution zakat infaq shodaqoh and waqf (ZISWAF) can be distributed through the intermediary of an organization authorized to manage it, as stated in “Republic of Indonesia Law no. 23 of 2011 regarding the management of zakat, infaq, shodaqoh and waqf in Indonesia is carried out by the National Amil Zakat Agency ( BAZNAS ) and the Amil Zakat Institute ( LAZ ). LAZIS which is engaged in social and da'wah is classified as LAZIS whose existence is still new in Kediri City so that it requires efforts to continue to grow and be able to compete with other LAZIS by making routine programmes that aim to increase donors. The purpose of this study is to determine how the routine programme of the ta'lim assembly is implemented and to determine the effectiveness and efficiency of the programme in increasing the number of donors. The method used in this research is qualitative with a qualitative descriptive approach. While data collection techniques using observation, interviews, and documentation. The data analysis used is data reduction and exposure and conclusion drawing. The results of the study state that the routine programme held by LAZIS Al-Haromain Kota Kediri has proven effective in increasing the number of donors, but it cannot be said to be efficient in meeting the target number of new donors each year.